-2(4s-4)-8=-2(9s+9)-3

Simple and best practice solution for -2(4s-4)-8=-2(9s+9)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4s-4)-8=-2(9s+9)-3 equation:


Simplifying
-2(4s + -4) + -8 = -2(9s + 9) + -3

Reorder the terms:
-2(-4 + 4s) + -8 = -2(9s + 9) + -3
(-4 * -2 + 4s * -2) + -8 = -2(9s + 9) + -3
(8 + -8s) + -8 = -2(9s + 9) + -3

Reorder the terms:
8 + -8 + -8s = -2(9s + 9) + -3

Combine like terms: 8 + -8 = 0
0 + -8s = -2(9s + 9) + -3
-8s = -2(9s + 9) + -3

Reorder the terms:
-8s = -2(9 + 9s) + -3
-8s = (9 * -2 + 9s * -2) + -3
-8s = (-18 + -18s) + -3

Reorder the terms:
-8s = -18 + -3 + -18s

Combine like terms: -18 + -3 = -21
-8s = -21 + -18s

Solving
-8s = -21 + -18s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '18s' to each side of the equation.
-8s + 18s = -21 + -18s + 18s

Combine like terms: -8s + 18s = 10s
10s = -21 + -18s + 18s

Combine like terms: -18s + 18s = 0
10s = -21 + 0
10s = -21

Divide each side by '10'.
s = -2.1

Simplifying
s = -2.1

See similar equations:

| 2(3+x)=85 | | 2(y+3)=5y-9 | | 5x-3[7-2(6x-7)-3x]=50x-63 | | 7+9r-2=8r+25-4r | | 4(2+x)=80 | | 4(2+x)=78 | | -9v-42=2(v+1) | | 4(2+x)=66 | | 4(2+x)=55 | | y-6.8=1.4(x-2) | | y-6.8=1.4(x-2) | | -23=3v+9-11v | | 6(t-3)+6t=4(3t+5)-9 | | 2s=b+p | | 2+389=y | | S=b+p | | 10-8x=16-7x | | 7z+4z=22 | | -6t-.8=5.2 | | z/18=-22 | | 5^(1/2)*2^(1/2) | | 9x-9=6x+9 | | 3(4+i)=63 | | 3(4+i)=62 | | 183x19/61x7/9 | | 1.75t^2-34.5t-241.5=0 | | y=-14+-4x | | 17+5/12X=100 | | 5u^2+24u-5=0 | | 3(2+x)=54 | | 1.95t^2-35.5t-248.5=0 | | 3(2+x)=50 |

Equations solver categories